1993
DOI: 10.1088/0953-2048/6/12/009
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced flux pinning in Ag-sheathed (Bi, Pb)2Sr2Ca2Cu3O10+ deltatapes by post-annealing

Abstract: A significant enhancement of J , in a magnetic fieid for Ag-sheathed Bi-Pb-Sr-Ca-Cu-0 (BPSCCO) tapes has been achieved by post-annealing at reduced temperature after processing. This post-annealing at reduced temperature introduced extra oxygen into the oxide superconductor. Weak links were eliminated and J, has been increased in the post-annealed tapes by a factor of 1.5 to 3 at 0 T over the normally processed tapes without post-annealing. The optimized J , values for the post-annealed tapes ranged from 30000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…The 2D pancake vortices are mainly confined in the Cu-O 2 layers [12]. Also Pb doping in the system improves the coupling between the Cu-O 2 layers by reducing the anisotropy and increasing the c-axis conductivity [2]. Substitution of each Yb atom at the Sr site of (Bi,Pb)-2212 supplies an additional electron to the system and reduces hole density.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2D pancake vortices are mainly confined in the Cu-O 2 layers [12]. Also Pb doping in the system improves the coupling between the Cu-O 2 layers by reducing the anisotropy and increasing the c-axis conductivity [2]. Substitution of each Yb atom at the Sr site of (Bi,Pb)-2212 supplies an additional electron to the system and reduces hole density.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there are two ways to enhance the flux pinning ability and hence the transport properties of (Bi,Pb)-2212 superconductor at high temperatures and high magnetic fields. One method is to reduce the anisotropy of the material [2], which strengthens the interlayer coupling between Cu-O 2 layers and increases the flux pinning potential. The other method is to introduce artificial defects, with the size matching the coherence length, as extra pinning centers.…”
Section: Introductionmentioning
confidence: 99%
“…Nomura et al [26] concluded that Jc values of Bi-2223 tapes increase with an increase in oxygen content. In previous work with the University of Pittsburgh [27], we also showed that cooling rate had a pronounced effect on transport J,.…”
Section: Pit Processingmentioning
confidence: 99%
“…However, Bi2223/Ag tape exhibits a poor J c behavior under magnetic fields, which impedes the commercialization of this material. J c decreases drastically with the increase of magnetic fields as a result of the motion of the magnetic flux lines, which arises from the weak flux pinning of the Bi-system materials [2]. Introducing artificial defects as extra pinning centers by means of physical and chemical doping is an effective method to improve the flux pinning ability of this material [3][4][5].…”
Section: Introductionmentioning
confidence: 99%